Improving competence for practice: a realist evaluation of co-produced master-level digital sexual health promotion courses for health and welfare professionals - Areskoug Josefsson, Kristina; Lindroth, Malin; Johannesen, Ane; Lunde, Gerd Hilde; Schultz, Kim Jana; Masterson, Daniel (Frontiers in Education, 2025)
IntroductionSparse education on sexual health promotion for health and welfare professionals can lead to unequal sexual health care provision, with related needs and rights being insufficiently met. To improve knowledge for health and welfare professionals, co-production and shared learning are essential, as students’ learning, and professional development are facilitated by effective partnerships between universities and workplaces.MethodsUsing a theoretical framework based on the concepts co-production, work-integrated learning, digital teaching and digital didactics, an initial programme theory was created. Thereafter, a realist evaluation was made of outcomes from five different digital master-level courses, all covering various aspects of sexual health promotion. Four data sources were used: 1) midway course evaluation from 32 students analysed with reflective thematic analysis, 2) focus group interviews with four teachers, analysed with reflective thematic analysis, 3) Students’ Attitudes to Sexual Health Extended survey pre- and post-test with 17 students, analysed with comparative statistics, and 4) learning analytics based on data from the digital tool FeedbackFruits, where interactions were analysed using a digital whiteboard).ResultsThe analysis resulted in a refined programme theory indicating that students found courses relevant for practice, became more comfortable talking about sexual health in practice and applied their learning in practice.DiscussionThe study supports the value of co-production in developing and delivering digital master-level courses in sexual health promotion for professionals, and the added value of work-integrated learning in this setting and highlights the need for digital literacy among both students and teachers. Confirmation or contradiction of the findings should be tested in this and other settings, and preferably with a larger sample.